Progress and application of salinomycin-induced cell autophagy in anti-cancer treatment - CHEN Siyuan; HU Ji'an (浙江大学学报. 农业与生命科学版)
Autophagy is a cell self-eating process that allows the orderly degradation and recycling of misfolded proteins and damaged organelles through lysosome. It plays a vital role in cells' adaptation to metabolic stress and homeostasis as well as the formation, development and treatment of tumors. Autophagy is a double-edged sword, both suppressing and facilitating tumorigenesis. For example, multiple benign tumors formed in the liver when autophagy gene Atg5 was mosaically deleted in mice. But at the same time, cancer cells can upregulate autophagy to survive under microenvironmental stress, promote tumor dormancy and increase their growth and aggressiveness.Salinomycin is a polyether ionophore antibiotic isolated from Streptomyces albus. Compared with lasalocid and monensin, salinomycin is less toxic, lower priced and less susceptible to drug resistance, which enables worldwide use to prevent chicken coccidiosis and promote the growth of ruminants. As an antimicrobial drug, salinomycin acts as an ionophore for K+ and Na+ ions and is able to alter cytoplasmic and mitochondrial membrane potentials, thereby inhibiting oxidative phosphorylation. Besides, salinomycin can activate a MutS homolog 1-dependent cell cycle checkpoint, leading to the ultimate death of the coccidial parasites.In 2009, salinomycin was reported to exert a powerful effect on breast cancer stem cells (CSCs), and it reduced the proportion of CSCs by more than 100 folds relative to paclitaxel. Up to now, it has been shown that salinomycin could effectively kill a variety of CSCs and multi-drug resistant cell lines by inhibiting Wnt/β-catenin signaling pathways, curbing cell cycle progression and reversing epithelial-mesenchymal transformation. Anticarcinogen can directly trigger apoptosis, autophagy and necrosis simultaneously. Most of cancer cell lines utilize autophagy to protect themselves from death after treatment with salinomycin. However, inhibiting autophagy through siRNA or PI3K inhibitor partially prevents cell death upon the addition of salinomycin in SW620 cells, indicating that autophagy induced by salinomycin can provoke cell death. The process of autophagy induced by salinomycin is complicated. Salinomycin can activate autophagy through different ways: 1) increasing intracellular reactive oxygen species (ROS), partly via ROS-JNK/AMPK signaling pathways;2) triggering mitophagy by damaging mitochondria;3) inducing endoplasmic reticulum stress to activate autophagy via AKT1-mTOR signaling pathway.In addition, salinomycin does not interfere with the autophagosome-lysosome fusion except suppressing autophagic flux at the late stage by diminishing the lysosome activity. Poor microenvironmental conditions, such as hypoxia, elevated interstitial fluid pressure, glycolysis, low pH and inflammatory cell infiltration, are common features of solid tumors, which are closely related to tumor progression, metastasis and therapy. Salinomycin significantly reduces F4/80+ and CD11B+ inflammatory cells of the tumor microenvironment in mice with pulmonary metastasis. Hypoxia, the focus of most studies, is involved in tumor angiogenesis and the generation and maintenance of CSCs. Low pH has a great influence on drug metabolism, rendering multi-drug resistant of the cancer cells. Autophagy is always upregulated in hypoxic and low pH regions of tumors for the metabolic adaptation of cancer cells. The efficiency of hydroxychloroquine, a late-stage autophagy inhibitor by disrupting lysosome acidification under clinical investigation, is strongly impaired in acidic tumor environments due to drug resistance. However, according to a new study, salinomycin could effectively inhibit autophagy flux under conditions of transient and chronic acidosis. This contributed to the elimination of several cancer cell lines and enhanced cytotoxic effects of salinomycin on CSCs. In short, the inhibition of autophagy flux by salinomycin leads to a considerable change in the tumor microenvironment, which makes salinomycin more potent in terms of the antitumor ability and provides new insights into drug combination.In sum, this paper reviews the antitumor mechanism and application of salinomycin in livestock, the relationship between autophagy and tumor, and the mechanism of autophagy induced by salinomycin.